Building Modern Networks - Noble, Steven (Packt Publishing Limited, 2017)
bGain the edge with SDN, NFV, network virtualization, and networking on clouds/bh2About This Book/h2ulliNavigate through the complexities of delivering modern networking services with practical techniques and solutions/liliBuild robust software defined networks and solve real-world problems involving challenges with next generation networks/liliDiscover the best practices used by top industry professionals for network-related architecture, services, and applications and secure your networks/li/ulh2Who This Book Is For/h2This book is for Network Engineers and Network Administrators who are taking their first steps when deploying software-defined networks.